Synthesis of magnetic nanostructures in different carbon matrices and post annealing with oxygen, nitrogen and argon - Vicente Pena Perez; Cristian Reynaga Gonzalez; Erick Villegas; Jonah Baughman; Lorena Aguirre; Franco Iglesias; Armond Khodagulyan; Oscar O. Bernal; Armen N. Kocharian (AIP Advances)
This study explores the innovative use of carbon matrices in the synthesis of magnetic nanographite, layered graphene stacks and graphene coated magnetic nanoparticles, with a focus on their morphological, structural, and magnetic prop-erties. To obtain a deeper insight into the influences of impurities in the graphene matrices on the magnetic properties of synthesized by pyrolysis, the two different metal free modifications of porphyrin such as tetraphenyl porphyrin (TPP) and tetra(4-carboxyphenyl) porphyrin (TCPP) with oxygen content (radical) were synthesized by subsequential post annealing with oxygen, argon and nitrogen, to characterize and investigate the role of oxygen and nitrogen content in graphene environment. The research highlights the significance of porphyrin and phthalocyanine metal free precursors and their metal counterparts for use as carbon matrices, examining their unique characteristics and applications in nanoparticle synthesis by sequential annealing. For example, the magnetization figure below for TPP indicates that the samples are diamagnetic at relatively high temperatures and large magnetic fields. Annealing at 150 °C for 180 min, specifically, for oxygen, it increases paramagnetic behavior and saturation. As for nitrogen, it increases coercivity. Employing advanced characterization techniques such as powder x-ray diffraction (PXRD), we analyzed the graphitization and porosity effects and layer sizes of nanographite and their impact on magnetic properties. A novel algorithm, integrating node extraction and 2D Gaussian mapping, is developed to enhance the accuracy of morphological analysis. Our findings reveal the critical role of graphene, and role of oxygen and nitrogen impurities in influencing the magnetic behavior of metal free carbon matrices and embedded nanoparticles, providing valuable insights into the design and development of advanced magnetic nanomaterials.